Pulmonary Thromboendarterectomy for Chronic Pulmonary Thromboembolism - Amna Abbas, Mazhar ur Rehman, Hina Aftab, Muhammad Athif Akram, Ghulam Kibriya, (Pakistan Journal of Medical & Health Sciences, 2023)
Pulmonary embolism in terms of causes of mortality is the third most common cause, when talking about cardiovascular diseases, yet most undiagnosed or misdiagnosed one. Among causes of pulmonary thromboembolism protein C deficiency is a rare one and idiopathic most common entity. In general population the incidence of severe protein C deficiency is about 1 in 500,000-750,000 people. We present a case of chronic pulmonary thromboembolism in young female of 23 years. She presented with history of dyspnea, dry cough and bilateral DVT of legs. On pulmonary CT diagnosis of massive pulmonary thrombus was made and her pulmonary thromboendarterectomy was done in our center. Conclusion: All patients with chronic pulmonary thromboembolic hypertension should be assessed for operability by proper referral to an experienced CTEPH (chronic thromboembolic pulmonary hypertension) team to determine if they are viable candidate for PEA (pulmonary endarterectomy). PEA is standard and recommended operative technique for treatment of CTEPH. Keywords: pulmonary endarterectomy, pulmonary embolism, protein C deviciency